Time Spent With Parents Varies With Early-Life Condition, but Does Not Predict Survival or Sociality of Juvenile Hihi - Franks, Victoria R.; McCready, Mhairi; Savage, James L.; Thorogood, Rose (Frontiers in Ecology and Evolution, 2019)
Many young birds die soon after fledging, as they lack the skills to find food and avoid predation. Post-fledging parental care is assumed to assist acquisition of these vital skills. However, we still lack empirical examples examining the length of time fledglings spend with parents, how they associate during this critical time, or whether such variation in the fledgling dependency period has consequences for the survival and behaviour of young as they navigate their first year of independent life. Here, we make use of observations and radio frequency identity (RFID) logs of visits to supplementary feeding stations to investigate how condition of fledgling hihi (stitchbird, Notiomystis cincta), a New Zealand passerine, predicts dispersal behaviour and tendency to follow parents during their two week post-fledging dependence period. We find that thinner fledglings followed their parents more closely in time when visiting feeding stations, compared to fatter siblings (all following ranged from 3 sec to 10 min). However, broods in poorer condition tended to disperse from the natal territory up to 6.5 days earlier than broods of fatter fledglings (all dispersed within 14 days). Our results did not find that sociality or survival during the first year of life differed depending on variation in fledgling behaviour; neither following parents closely nor dispersing later predicted each bird’s number of associates (degree), or survival over winter. These results suggest that fledglings may be able to compensate for early differences in condition with behaviour, either during the post-fledging dependence period or when independent.